Peningkatan Kemampuan Literasi Numerasi Siswa SMP Swasta Islam Terpadu Karakter Anak Shalih Kota Padang - Haripamyu Haripamyu; Noverina Alfiany; Arrival Rince Putri; Susila Bahri; Monika Rianti Helmi (Warta Pengabdian Andalas, 2023)
Numerical literacy is an ability that requires an understanding of basic mathematical concepts and skills. Private Integrated Islamic Junior High School (SMPS IT) "Karakter Anak Shalih" (KAS) has not implemented the Minimum Competency Assessment (MCA) of the 2022/2023 school year, which will be held in 2023. The preparations for MCA implementation should be started in 2022. One of the problems schools encounter is how to prepare the students to conceive numeracy literacy for MCA. The Community Service Activities (CSA) of the Department of Mathematics and Data Science of Universitas Andalas aims to accompany teachers and students to increase students' understanding of basic concepts and skills in mathematics, providing socialization and assistance to teachers and students regarding numeracy literacy knowledge, and supporting schools to improve learning process services. Those activities were carried out in three main stages, namely, the preparation stage, the implementation stage, and the activity evaluation stage. The results of this CSA activity were evaluated by observing the students' understanding of mathematical concepts, numeracy literacy, and improving services that support the learning process. Based on the CSA activities, it was concluded that mentoring activities must be continued to assist schools in dealing with MCA.